IDENTIFICAÇÃO DO PERFIL DE RISCO CARDIOVASCULAR EM TRABALHADORES DE UMA INDÚSTRIA AUTOMOBILÍSTICA: APLICAÇÃO DA TABELA DA SOCIEDADE AMERICANA DE CARDIOLOGIA - Lelis Filho, Raimundo (2006)
The progressive aging of the world population has been causing the increase in the prevalence of cardiovascular diseases, especially the coronary artery disease cardiopathy. In Brazil, in 2002, 31,52% of the deaths occurred were connected to the cardiovascular system (DATASUS, 2005). Based on this observation, the author of this paper developed his research with the objective to identify the risk factors related to the coronary artery disease and, thus, to propose future measures that may reduce the prevalence of this disease and its complications amidst the population under study. In this paper, two hundred seventy two individuals were analyzed, all of which employees of an automobile industry, with a predominance of young adults (age median of 36), with 90,4% mens. For the identification of the coronary risk profile, the American Heart Association (AHA) Table was used. Amongst the factors that were analyzed in the table, the following characteristics were found: 54% did not do any physical activity; 85% were overweight or showed signs of obesity; 7% had cases of coronariopathy in the family; 5% presented glycemia above 135 mg/dL (NV up to 100 mg/dL); 30% of the individuals showed cholesterol levels above 200 mg/dL (NV up to 200 mg/dL); 10% were hypertensive. Unlike the statistics for the Brazilian population, only 10% of the individuals were found to smoke. On analyzing the distribution of the individuals as to the risk levels listed in the AHA Table (six categories considered), the author found the following numbers in the population under study, according to the following categories in which they fell: riskless (37 individuals), potential risk (158 individuals) and moderate risk (77 individuals). Individuals were not classified in the high risk , danger and maximum risk categories. It is important to point out that, although the population under study was young and the individuals were not included in the greater risk categories, 86,4% of them showed coronariopathy risk to a certain degree. The AHA Table was a useful tool in the identification of the main coronarian risk factors in the population under study, despite the difficulty found in the stratification of some of the variables included in the analysis.